PERAN PENGADILAN HUBUNGAN INDUSTRIAL PADA PENGADILAN NEGERI PADANG KELAS IA DALAM MEMBERIKAN KEPASTIAN HUKUM TERHADAP PERKARA PEMUTUSAN HUBUNGAN KERJA - sinaga, rustan (Universitas Ekasakti, 2018)
Termination of employment has a very complex impact and tends to cause disputes between employers and workers. in various laws and regulations, mechanisms and procedures for termination of employment have been regulated with the aim that both businessman and workers can maintain their normative rights. Since the enactment of Law No. 2 of 2004 concerning Industrial Relations Disput, the handling of employment disputes is the authority of the Industrial Relations Court at the local District Court. in addition to the judicial route (litigation) the settlement of disputes over termination of employment can also be settled outside the court (non litigation).In this study the author will focus on the settlement through justice (litigation). the issues discussed in this paper are the Roles of the Industrial Relations Court in Providing Legal Certainty to Termination of Employment (PHK) and the Implementation of Industrial Relations Court Decision by the Parties. in Writing this thesis the author uses the research of empirical law with normative juridical approach method supported by empirical juridical approach. Legal material collection techniques are carried out by means of library research and field research.The role of the Industrial Relations Court in the Padang Class IA Court, has resolved the case brought by the justice seekers to them, thereby granting the legal status in accordance with Law Number 2 of 2004 on Industrial Relations Dispute Settlement.The implementation of the Industrial Relations Court Decision by the Parties has not been carried out optimally in according to the PHI decision in the Padang Class IA District Court, because there are no strict sanctions against disobedience of the parties who did not carry out the decision, namely the employer as the convicted party to carry out the PHI decision in the Padang Class IA District Court. Therefore, against those who do not comply with the ruling IRC, should be subject to strict sanctions in the form of temporary revocation of business licenses, and government needs to make regulations to regulate the sanctions against parties who do not comply with the ruling of the IRC in Padang Class IA Court on particular and the Industrial Relations Court at the General Courts in general.